Modulation of Carbon Nanotube Metal Contacts in Gaseous Hydrogen Environment. (27th March 2014) - Usgaocar, A. R.; Chong, Harold M. H.; de Groot, C. H.
Abstract : Carbon nanotubes (CNTs), contacted by electrodeposited Pd0.59 Ni0.41 alloys, are characterised using electrical measurements and Raman spectroscopy. The high workfunctions of Nickel and Palladium form an ohmic contact with the CNT valence band, but the contact properties change on Hydrogen exposure due to a reduction in the PdNi workfunction and the realignment of the PdNi Fermi level with the CNT band structure. A PdNi contacted semiconducting CNT exhibited significantly lower currents after Hydrogen exposure while a metallic CNT exhibited a small current increase. The semiconducting and metallic natures of the CNTs are confirmed by their Raman spectra. This study demonstrates a technique for modulating the PdNi-CNT contact and differentiating between semiconducting and metallic CNTs via contact modulation. It also provides experimental evidence of the theoretical allocation of features in the CNT Raman spectra.